Television food and beverage marketing to children in Costa Rica: current state and policy implications - Zamora Corrales, Irina (2019)
Objective: To examine the frequency of television (TV) food and beverage advertisements (F&B ads) to which children (4–11 years) are likely exposed and the nutrient profile of products advertised. Design: TV broadcasting between September and November 2016 was recorded (288 h of children’s programming; 288 h of family programming) resulting in 8980 advertisements, of which 1862 were F&B ads. Of those, 1473 could be classified into one of the seventeen food groups, and into permitted/non-permitted according to the WHO-EU nutrient profile model. Persuasive marketing techniques used were also identified. Setting: TV programming was recorded for four weekdays and four weekend days, between 06.00 and 00.00 hours (576 total hours), for four channels (two national and two cable), in Costa Rica. Results: Mean (SD) number of F&B ads/h was greater in cable than national channels (3·7 (0·4) v. 2·8 (0·4), P < 0·05) and during children’s peak viewing hours (4·4 (0·4) v. 2·9 (0·3)). Of F&B ads classified with WHO-EU nutrient profile model (n 1473, 71·1 %), 91·1 % were non-permitted to be marketed to children. Categories most frequently advertised were ready-made/convenience foods (16 %), chocolates/confectionery/desserts (15 %), breakfast cereals (14 %), beverages (15 %), edible ices (9 %) and salty snacks (8 %). Non-permitted F&B ads were more likely to use promotional characters, brand benefit claims, and nutrition and health claims than permitted F&B ads. Conclusions: Children watching popular TV channels in Costa Rica are exposed to a high number of unhealthy F&B ads daily. Our findings help justify the need for regulatory actions by national authorities.